2021
DOI: 10.1016/j.ijwd.2021.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in lupus erythematosus female patients with cutaneous lesions in Antananarivo, Madagascar

Abstract: Background: Lupus erythematosus (LE) is a chronic autoimmune disease that affects more women than men. The quality of life (QoL) of patients with lupus erythematosus and skin manifestations is impaired, but little is known about Malagasy patients. Objective: This study aimed to assess the impact of cutaneous lesions on the QoL of patients who present with LE. Methods: A transversal study, during 3 months, was conducted in patients who presented with LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 15 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…In contrast, existing literature has identified variable associations between income and health-related quality of life ( 7 , 30 , 33 , 35 ). An annual income < $10,000 was associated with a lower quality of life in the SKINDEX-29+3 functioning and symptom domains in three studies ( 7 , 30 , 35 ).…”
Section: Income Education and Geographic Locationmentioning
confidence: 89%
See 4 more Smart Citations
“…In contrast, existing literature has identified variable associations between income and health-related quality of life ( 7 , 30 , 33 , 35 ). An annual income < $10,000 was associated with a lower quality of life in the SKINDEX-29+3 functioning and symptom domains in three studies ( 7 , 30 , 35 ).…”
Section: Income Education and Geographic Locationmentioning
confidence: 89%
“…Hesselvig et al actually found that men with CLE had a higher risk of depression than women ( 27 ). However, a small cohort of LE patients in Madagascar did not find any significant correlations between gender and Dermatology Life Quality Index (DLQI) scales ( 33 ). Similarly, a CCLE cross-sectional cohort study in Georgia did not find significant differences in risk and severity of depression by gender ( 26 ).…”
Section: Gendermentioning
confidence: 97%
See 3 more Smart Citations